The biological activities of Citrus species in crop protection - Marta Lo Vetere; Valeria Iobbi; Anna Paola Lanteri; Andrea Minuto; Giovanni Minuto; Nunziatina De Tommasi; Angela Bisio (Journal of Agriculture and Food Research, 2025)
Citrus, a globally cultivated genus, is rich in bioactive compounds like flavonoids and essential oils, known for their health benefits and antimicrobial properties. This review explores the potential of Citrus extracts, essential oils, and bioactive compounds in enhancing crop protection. Integrating these natural products into pest management strategies has the potential to reduce reliance on chemicals, address resistance issues and promote sustainable agriculture and rural economies. Chemicals have been widely used for crop protection, providing immediate benefits but also posing significant risks to human health and the environment, such as water and air pollution, soil degradation and the development of resistant pest strains. This comprehensive review highlights the importance of citrus-based solutions in modern agriculture, which aims to balance productivity with environmental and health concerns. It also summarises the broad spectrum of activity of these fruits against a wide range of plant micro-organisms (insects and mites, bacteria, fungi, viruses, nematodes) and weeds. As research continues to explore their full potential, Citrus waste is poised to play a crucial role in advancing sustainable and resilient agricultural practices.